Instantaneous Decrease in Left Ventricular Afterload during Transcatheter Aortic Valve Implantation Results in Immediate Changes in Left Ventricular Strain. Issue 5 (17th December 2015) - Swan, Amy; Prakash, Roshan; Chew, Derek P.; Perry, Rebecca; Sinhal, Ajay; Selvanayagam, Joseph B.; Joseph, Majo X.
Abstract : Severe aortic stenosis causes chronic increased afterload on the left ventricle (LV) resulting in myocardial hypertrophy and ultimately dysfunction if left untreated. Transcatheter aortic valve implantation (TAVI) immediately decreases the afterload on the LV by reducing the pressure gradient through the aortic valve. In our study, we aim to evaluate immediate changes in LV mechanics using intra‐procedural transesophageal echocardiography (TEE) to assess circumferential and radial strain via speckle tracking. Intra‐operative TEE was performed during TAVI for 53 patients (mean age 84 ± 8 years). Two‐dimensional images in the transgastric view were acquired at the level of the papillary muscle. Circumferential and radial strain was calculated using speckle tracking with Philips Qlab software. Global LV afterload was measured by calculating valvulo‐arterial impedance (Zva). Immediately post‐TAVI, there was a change in both radial strain rate (Pre: 0.73 ± 0.04 vs. Post: 0.88 ± 0.04 per second, P < 0.001) and circumferential strain rate (−0.53 ± 0.04 (pre) vs. −0.74 ± 0.04 (post) per second, P < 0.001). There was also an immediate improvement in circumferential global strain parameters (−14.5 ± 5% (pre) vs. −16.0 ± 4.7% (post), P < 0.05), whereas there was no significant change seen in global radial strain (15.6 ± 0.8% (pre) vs. 15.2 ± 0.9% (post), P = 0.69). No significant change was seen in LV ejection fraction (51.5 ± 14.2% (pre) vs. 52.1 ± 14.0% (post), P = 0.77). Speckle tracking using TEE images is feasible and identifies significant improvements in LV strain and strain rate immediately following TAVI that is not detected by conventional measure of LV function.